Influence of WRF-Lake Model on Summer Atmospheric Boundary Layer Simulation in Nam Co Lake Area under Different Subgrid Parameterization Schemes - Ziyi WANG; Xianyu YANG; Yaqiong LÜ; Xianhong MENG; Lihuan WANG (Gaoyuan qixiang)
In this study， the improvements of lake dynamic module parameters in the literature were added to WRF-Lake （WRF4.4.1） at first， then six microphysical schemes， five cumulus convection schemes and two boundary layer schemes were selected.A total of 60 WRF-Lake simulations with different parameterization schemes were carried out from July 5 to 13， 2008 in the Nam Co Lake area.Sensitivity experiments were conducted to comparatively analyze the effects of different parameterization scheme combinations on atmospheric boundary layer variables.The "ranking method" was employed to comprehensively evaluate the simulation capabilities of different parameterization schemes in the summer atmospheric boundary layer over Nam Co Lake.The results indicated that the model captures the overall spatial and temporal distribution characteristics of the summer average two-meter temperature in Nam Co.However， the simulated values of the two-meter temperature over the lake were higher than the land surface data.Due to the selection of cumulus convection parameterization schemes and the impact of model performance， there was significant differentiation in the simulation effects of precipitation among experimental groups， leading to varying degrees of overestimation of daily precipitation.The daily average variations of latent heat fluxes showed the best correlation with observational values， while sensible heat and wind direction exhibited relatively good performance， and wind speed showed the least satisfactory results.Overall， comprehensive analysis of the simulation capabilities of each experimental group for the summer atmospheric boundary layer over Nam Co Lake revealed that Scheme 58 （SBU-Tiedtke-MYNN3） performed the best in simulations of 2 m temperature， daily precipitation， 10 m wind fields， and surface heat fluxes.The RMSE value for two-meter temperature and daily precipitation was 2.33 °C and 10.48 mm， respectively.The correlation coefficient for the daily average variation of 10 m wind speed was -0.41， and the ratio of standard deviations was 0.94.The correlation coefficient for the daily average variation of 10 m wind direction was 0.59， and the ratio of standard deviations was 0.73.The correlation coefficient for the daily average variation of sensible heat flux was 0.94， and the ratio of standard deviations was 1.89.The correlation coefficient for the daily average variation of latent heat flux was 0.89， and the ratio of standard deviations was 0.91.Therefore， it is recommended to use the aforementioned grid parameterization scheme for simulating the summer atmospheric boundary layer over the region of Lake Nam Co.